If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + 9a = 8(1 + a) + -13 -18 + 9a = (1 * 8 + a * 8) + -13 -18 + 9a = (8 + 8a) + -13 Reorder the terms: -18 + 9a = 8 + -13 + 8a Combine like terms: 8 + -13 = -5 -18 + 9a = -5 + 8a Solving -18 + 9a = -5 + 8a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-8a' to each side of the equation. -18 + 9a + -8a = -5 + 8a + -8a Combine like terms: 9a + -8a = 1a -18 + 1a = -5 + 8a + -8a Combine like terms: 8a + -8a = 0 -18 + 1a = -5 + 0 -18 + 1a = -5 Add '18' to each side of the equation. -18 + 18 + 1a = -5 + 18 Combine like terms: -18 + 18 = 0 0 + 1a = -5 + 18 1a = -5 + 18 Combine like terms: -5 + 18 = 13 1a = 13 Divide each side by '1'. a = 13 Simplifying a = 13
| 10xy-4y= | | 12(v-13)=2v-66 | | 4t^2+24t-27=0 | | 24+y*2=x | | -25=4(5k-7)+3(1+3k) | | 6(2x+1)=12x+3 | | -2(1-10n)=-52+10n | | 48.3/17.3 | | -2(1-10n)=-27+14b | | 0.6x+1.43=x-6.22 | | 6(4b+2)+3b=-27+14b | | (2/3x)-4=5/6 | | 2/3x-4=5/6 | | 5x-25=2x-38 | | -26=4(8n+6)-2(3n-1) | | 7(7k-9)+5k=8k+29 | | 2(-2p+3)-5(p+7)=34 | | -54/g=3 | | 7a-3b+5= | | -34+x=6(-8-x) | | 6x/-4=-.3 | | -23-8x=-2(x-7)-7 | | (y^4/5)^2 | | 7900=40x+4000 | | k-4=-7 | | 3(2x-1)=3-2(x-1) | | 4=22x | | -2.2d+16.95=-3.8d-14.41 | | d/-7-8 | | -18+c=-14 | | differentiate:dy/dx=3x^2 | | f(2.3)= |